Negative catheter angiography after vascular contrast extravasations on computed tomography in blunt torso trauma: an experience review of a clinical dilemma - Yuan, Kuo-Ching (BioMed Central, 2012)
BACKGROUND: Catheter angiography is often arranged when vascular contrast extravasations on computed tomography (VCEC) presents after blunt torso trauma. However, catheter angiograph can be negative for bleeding and further management about this condition is not well discussed. The purpose of this study was a review of our experience of this discrepancy and to propose management principle. METHODS: We conducted a retrospective analysis of patients who received catheter angiography due to VCEC after blunt torso trauma at a level one trauma center in Taiwan from January 1, 2006 to December 31, 2009. Patient data abstracted included demographic data, injury mechanism, Injury Severity Score, vital signs and laboratory data obtained in the emergency department, CT and angiography results, embolization status, rebleeding and outcome. Analysis was performed according to angiographic results, VCEC sites, and embolization status. RESULTS: During the study period, 182 patients received catheter angiography due to VCEC, and 48 (26.4%) patients had negative angiography. The kidney had the highest incidence (31.7%) for a discrepant result. Non-selective proximal embolization under negative angiography was performed mostly in pelvic fracture and spleen injury. Successful treatment without embolization after negative angiography was seen in the liver, kidney and pelvic fractures. However, some rebleeding happened in pelvic fractures with VCEC even after embolization on negative angiography. CONCLUSIONS: A negative catheter angiography after VCEC is possible in blunt torso trauma, and this occurs most in kidney. Embolization or not under this discrepancy requires an integrated consideration of injury site, clinical presentations, and the risk of rebleeding. Liver and kidney in blunt torso trauma can be managed successfully without embolization when catheter angiography is negative for bleeding after VCEC.